Предмет: Математика, автор: Lilpumpgih

(-2)²+(-2)³+(-2)⁴=?
3³+(-2)²+(-3)³+2²=?
(-2)²-(-3)³+4²-5³=?
(-2)³•(-5)³-3²•(-1)⁵+2³•(-3)²=?

Ответы

Автор ответа: Аноним
0

\displaystyle 1)(-2)^2+(-2)^3+(-2)^4=(1-2+(-2)^2)(-2)^2=(1-2+4)*2^2=3*4=12\\\\2)3^3+(-2)^2+(-3)^3+2^2=27+4-27+4=8\\\\3)(-2)^2-(-3)^3+4^2-5^3=4-(-27)+16-125=4+27+16-125=-78\\\\4)(-2)^3*(-5)^3-3^2*(-1)^5+2^3*(-3)^2=-2^3(-5^3)-3^2(-1)+8*3^2=\\\\10^3+3^2+8*3^2=1000+9*3^2=1000+3^2*3^2=1000+3^4=1000+81=1081

Похожие вопросы
Предмет: Английский язык, автор: Style121